2017
DOI: 10.1002/hep4.1053
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular intrahepatic portosystemic shunt does not independently increase risk of death in high model for end stage liver disease patients

Abstract: Physicians often exclude patients with a model for end‐stage liver disease (MELD) score ≥ 18 from a transjugular intrahepatic portosystemic shunt (TIPS) procedure due to the concern for higher risk of death. We aimed to determine if TIPS increased the risk of death in these patients. We analyzed the interaction between TIPS and MELD in 106 patients with TIPS and 79 with intractable ascites without TIPS. We performed Cox proportional hazard regression, including both TIPS and MELD as time‐dependent covariates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The positive outcome and decrease in incremental risk of death ultimately benefit this subgroup of patients as well as demonstrated in some of the newer studies. 15 …”
Section: Discussionmentioning
confidence: 99%
“…The positive outcome and decrease in incremental risk of death ultimately benefit this subgroup of patients as well as demonstrated in some of the newer studies. 15 …”
Section: Discussionmentioning
confidence: 99%
“…31 Similarly, Spengler et al recently analyzed the interaction between MELD score and TIPS placement in patients with refractory ascites. 32 Compared with those who did not receive a TIPS, as MELD increased, the risk of death was progressively lower than expected in patients who received TIPS. Patients with high MELD scores (>18) who received a TIPS had a mortality risk that was 51% lower than expected in the first 6 months following TIPS placement.…”
Section: Patient Selectionmentioning
confidence: 94%
“…MELD score classifies candidates undergoing TIPS based on objective laboratory findings, in contradistinction to the Child-Pugh classification which contains a subjective assessment that can lead to inter-observer variability based on clinicians' judgement. 29 30 31 32 Prior studies have shown that a MELD score of ≥18 is considered a high threshold cut-off for TIPS placement due to elective post-TIPS mortality, compared with a MELD <18 33 . However, a recent single center, retrospective study concluded that the mortality was ∼50% lower than expected when TIPS was performed in patients with MELD scores >18, suggesting the need for a prospective RCT.…”
Section: Management Of Refractory Ascitesmentioning
confidence: 99%